1010. KLASEA CERINTHIFOLIA: Compositae. (8th March 2022) - Hind, Nicholas; Moore, Richard; King, Christabel
Summary: Klasea cerinthifolia (Sm.) Greuter & Wagenitz (Compositae: Cardueae: Centaureinae) is described and illustrated, a full synonymy provided, and its taxonomic position discussed. Cultivation requirements are also outlined and, although apparently unavailable commercially, it may be found in a few botanical gardens. The species exhibits an interesting trimorphic leaf morphology, with the upper cauline leaves or bracts resembling the appearance of Cerinthe in the Boraginaceae. The genus Klasea is discussed, from its inauspicious beginnings to a genus of about 50 species in ten sections; K. cerinthifolia is placed in sect. Schumeria (Iljin) L. Martins, of which it is type. The species' long history in the literature is discussed, and the clear historical confusion with Centaurea behen L. is covered in detail. Literature research, and specimen examination, has shown that the two taxa are sympatric across a large part of their range, but are fairly straightforward to tell apart generically, although looking somewhat similar. The name Centaurea behen has previously been ineffectively neotypified, even though original material was cited in Linnaeus's protologue. It was later lectotypified, based on an ambiguous woodcut illustration but the lectotype illustration does not allow for critical identification. An epitype is designated here so as to avoid this continuing nomenclatural saga.